Altitudinal distribution and habitat use of the common wall lizard Podarcis muralis (Linnaeus, 1768) and the Horvath’s rock lizard Iberolacerta horvathi (Méhely, 1904) in the Kočevsko region (S Slovenia) - Anamarija Žagar (Natura Sloveniae)
The study reports on the distribution and habitat use of two lizard species in the Kočevsko region: Horvath’s rock lizard and common wall lizard. Extensive sampling across an altitudinal span of 200 to 1,100 m a.s.l. in the study area revealed 62 localities with populations of both or either species. At 11 of these localities (18%) species occurred in syntopy, at 42 locations (68%) only common wall lizards were found, while at 9 locations (14%) only Horvath’s rock lizards were recorded. Both species occurred across the entire altitudinal span but exhibited an opposite pattern of relative abundances and frequencies, which increased with increasing altitude in Horvath’s rock lizard and with decreasing altitude in common wall lizard. The habitat use of common wall lizard was more general (it was found in seven habitat types) than Horvath’s rock lizard that was registered only in three habitat types with rocks.